2014
DOI: 10.5152/eajm.2014.39
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in School Children in Mardin, South-Eastern of Turkey

Abstract: Objective: To determine the prevalence of the metabolic syndrome (MES) in a school children population. Materials and Methods:Three thousand four hundred and sixty children aged between 7 and 15 in three elementary schools in the city of Mardin, located in the south-eastern region of Turkey, were included in this study in April and May 2011. Age, gender, height, weight, waist circumference (WC), hip circumference, waist/hip ratio, systolic and diastolic blood pressure were measured and a variety of blood tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…In the present study the prevalence of MS in obese children was 36.2% which is higher than the Chinese, 24 Egyptian 25 and Turkish children, 13 but less than three other studies from Iran 26 , 27 and Turkey. 28 …”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…In the present study the prevalence of MS in obese children was 36.2% which is higher than the Chinese, 24 Egyptian 25 and Turkish children, 13 but less than three other studies from Iran 26 , 27 and Turkey. 28 …”
Section: Discussioncontrasting
confidence: 75%
“…12 , 20 Other studies have reported a slightly higher prevalence of MS in females compared to males. 13 , 19 , 21 However, no meaningful difference in the prevalence of MS based on sex was to other studies from Iran. 18 , 22…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Prevalence rate of MetS among children and adolescents is very much dependent on the various definitions offered. This figure was 8.9% in 8 to 9-year-old Brazilian children by adopting specific criteria for age ( 85 ), 6.5% in Mexico using modified ATP III criteria ( 86 ), 6.3% in 7–15-year-old children based on IDF criteria in Turkey ( 87 ), 4% based on the modified-ATPIII criteria in Tunisia ( 88 ), 6.6% using the De Ferranti definition among elementary school children of China ( 89 ), 4.2% using modified ATPIII criteria in north India ( 90 ) and 16.5% to 18% among school-aged children in Pakistan based on various definitions ( 91 ). The absence of a comprehensive and universal definition of MetS in children and adolescents could, to some extent be a factor in the difference between the reported rates of prevalence from the numerous studies throughout the world.…”
Section: Discussionmentioning
confidence: 99%